Rheology of modified water based Isinya and Amboseli Clays: Effect of sodium carbonate and sodium carboxymethylcellulose. - Weramwanja, Peter M.; Musuva, Jeremiah K.; Kihiu, John M.; Borode, Joseph O.; Olubambi, Peter A.; Mibei, Geoffrey K. (My University, 2018)
Two Kenyan state owned entities are investing heavily in geothermal power exploration in Rift valley, to find enough steam for developing geothermal plants with capacities of up to 10,000 MW. This will require more than 1,000 wells to be drilled using Bentonite as a drilling mud. The aim of this study is to evaluate the suitability of six different samples of bentonite from two different geographical regions (Isinya and Amboseli) in Kenya, for possible use in well drilling in their raw and modified forms. Particle –particle interactions in the clay suspensions was considered in the study of the rheological properties. The samples were modified with Na2CO3(reduce the amount of calcium) and CMC (reduce the amount of water lost to the formations) in various concentrations. It was observed that flow properties (apparent and plastic viscosity, shear stress and yield point) changed depending on the clay source, additive chemical composition and concentration.
Keywords: Bentonite; Rheology; Carboxymethylcellulose,; Viscosity; Sodium carbonate; Shear stress